Penggunaan Kalimat Berdasarkan Makna dalam Kegiatan Diskusi Pembelajaran Bahasa Indonesia Siswa Kelas VII - Putri Al Farizka; Iing Sunarti; Siti Samhati (Jurnal Kata (Bahasa, Sastra, dan Pembelajarannya), 2019)
This research aims to describe the use of sentences based on their meanings used by students in the discussion activity in Indonesian Language learning for grade VII students of Public Junior High School 23 Bandar Lampung academic year of 2017/2018. This research applied a qualitative descriptive method. The data source in this research was in form of sentences spoken by students in grade VII during the discussion activity in Indonesian Language learning at Public Junior High School 23 Bandar Lampung. The data collection techniques were carried out through observation, documentation, and audio recording. The data analysis technique was done using a flow model. The results of the research indicated that the use of sentences based on their meanings used by students, were grouped as follows: 1) Declarative sentences, 2) Imperative sentences, 3) Interrogative Sentences, 4) Explosive Sentences. The results of the analysis on the use of sentences based on their meanings showed that the most dominant sentences used by students in this research were declarative sentences.Penelitian ini bertujuan untuk mendeskripsikan penggunaan kalimat berdasarkan makna yang digunakan oleh siswa dalam kegiatan diskusi pada pembelajaran Bahasa Indonesia siswa kelas VII SMP Negeri 23 Bandar Lampung tahun ajaran 2017/2018. Metode yang digunakan ialah metode deskriptif kualitatif. Sumber data pada penelitian ini berupa kalimat siswa kelas VII saat berdiskusi dalam kegiatan diskusi pada pembelajaran Bahasa Indonesia di SMP Negeri 23 Bandar Lampung. Teknik pengumpulan data dilakukan dengan observasi, dokumentasi, dan rekaman berupa audio. Teknik analisis data menggunakan model alir. Hasil penelitian ini menunjukkan bahwa penggunaan kalimat berdasarkan makna yang digunakan siswa yaitu, 1) Kalimat deklaratif, 2) Kalimat imperatif, 3) Kalimat Interogatif, 4) Kalimat Ekslamatif. Hasil analisis penggunaan kalimat berdasarkan makna yang lebih dominan dalam penelitian ini ditemukan ialah kalimat yang bermakna deklaratif.Kata kunci: Penggunaan kalimat, berdasarkan makna, dan pembelajaran.